Innovative to the core : stories from China and the world - Fernandez, Juan Antonio; David, Emily M.; Chen, Shaohui (Emerald Publishing Limited, 2022)
Based on extensive interviews with industry leaders, Innovative to the Core: Stories from China and the World describes the components of innovative cultures, including both national culture and organizational culture and how they compare to the China model. Distinguishing between innovation and related concepts, chapters detail how talent management, leader behaviors, organizational systems, and company culture must combine and interact to create environments that are innovative to the core. Innovative to the Core displays how most innovative countries and companies are led by visionary and entrepreneurial servant leaders and have agile cultures that feature psychological safety, open communication, and diversity.